(3GdagOI GdLGeYI aj fXe GdYbjOI GdfGaYIs - (3UGdM Hf GdUOjb GdfeGRis; (3YHO GdQMef Hf CMeO Hf YHO GdZaGQ, CHh GdaVd, nYoVO GdOjf GdEjLj,J (B756 (3g` s
(3ChdgG (B:s
(3bGd GdfeGRi GdabjQ UGdM CMeO QHi Gddg agh GdaGJM hgPg ceG JQi CQLhRI LGeYI hGVMI hLjRg fXeJ ajgG HYO GdESJNGQI YbjOI UMjMi eNJGQI s
(3BNQgG (B:s
(3Ke UdGI Gddg hGdSdGe eG EgJR ZUf Eh TOG MeGe Ydi GdfHi GdeUWai eMeO hidg Cgd GdJbi hGdSDOO s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG JUMjMGJs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds